Ensuring volunteer impacts, legacy and leveraging is not "fake news": Lessons from the 2015 FIFA Women's World Cup. Issue 2 (23rd January 2020) - Dickson, Tracey J.; Darcy, Simon; Pentifallo Gadd, Caitlin
Abstract : Purpose: This study aims to explore the legacy potential of the FIFA Women's World Cup (FWWC) 2015, for the host communities across Canada. Design/methodology/approach: The mixed-methods study included a link to an online anonymous survey being sent to all volunteers at the FWWC that explored their prior volunteering experience, motivations for volunteering, perceived skill development and future volunteering intentions. Documents were reviewed, and key stakeholders were interviewed. Findings: The results support previous research that mega-sport event (MSE) volunteers are typically older females with prior volunteering experience. Those most likely to indicate they wanted to volunteer more are younger volunteers without prior volunteering experience. While legacy was discussed as a desired outcome, this was not operationalised through strategic human resource strategies such as being imbedded in the position descriptions for the volunteer managers. Research limitations/implications: As this study was conducted in the real-world context of a sport event, the timing of the survey was determined by the organising committee. Practical implications: Mega sport events typically draw upon existing host-city social and human capital. For future event organising committees planning for and delivering a volunteer legacy may require better strategic planning and leveraging relationships with existing host-city volunteer networks. In the context of a single sport, women's MSE, multi-venue, multi-province event, greater connection was required to proactively connect younger women for volunteers to their geographic sport and event volunteering infrastructure. Originality/value: This is the first research of volunteers for the largest women's mega single-sport event. There are three theoretical contributions of the paper to: the socio-ecological lens, motivational theory of single event MSE and the contribution of social and human capital to understandings of legacy.